2011
DOI: 10.1016/j.jvs.2010.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon case volume, not institution case volume, is the primary determinant of in-hospital mortality after elective open abdominal aortic aneurysm repair

Abstract: The primary factor driving the mortality reduction associated with case volume after open AAA repair is surgeon volume, not institution volume. Regionalization of AAAs should focus on open repair, as EVAR outcomes are equivalent across volume levels. Payers may need to re-evaluate strategies that encourage open AAA repair at high-volume institutions if specific surgeon volume is not considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 28 publications
1
68
1
4
Order By: Relevance
“…Specific details such as these are not available in the NIS. However, previously published data from the NIS [24][25][26][27] has shown that hospital size is not associated with improved outcomes but rather that surgeon volume and specialized practice are associated with reduced inpatient morbidity, length of stay, and cost. The present results suggest that hospital type, location, and size may not be as important as surgeon experience.…”
Section: Commentmentioning
confidence: 95%
“…Specific details such as these are not available in the NIS. However, previously published data from the NIS [24][25][26][27] has shown that hospital size is not associated with improved outcomes but rather that surgeon volume and specialized practice are associated with reduced inpatient morbidity, length of stay, and cost. The present results suggest that hospital type, location, and size may not be as important as surgeon experience.…”
Section: Commentmentioning
confidence: 95%
“…[3][4][5][6]). However, the magnitude of the volume-outcome relation varies between conditions and the outcome is not only dependent on hospital volume, but also on surgeon volume and the level of specialization [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first endovascular repair of an abdominal aortic aneurysm by Dr. J.C Parodi in 1991, endovascular approaches for aortic surgery have become increasingly common [7][8][9][10]. There has been an 850% increase in iliac artery angioplasty and stenting from 1996-2000 in the Nationwide Inpatient Sample (NIS), while open operations declined by 15% over the same period [11].…”
Section: Discussion Incidencementioning
confidence: 99%